Dampak Hoax di Media Sosial Facebook Terhadap Pemilih Pemula - Aminah Aminah; Novita Sari (Jurnal Komunikasi Global, 2019)
Facebook social media is one of the media that is very influential in people's lives today. Using Facebook, the dissemination of information can be quickly conveyed to the public, especially to Facebook users. This raises concern from users in filtering information to avoid fake news. This research aims to explain to the impact of fake news on Facebook on beginner voters who have a right to vote in presidential and legislative elections in Panga District, Aceh Jaya. This study used a qualitative descriptive method. The data were collected by interviewing nine informants. The results of the study showed that Facebook is often used by beginner voters to obtain information related to electoral affairs. The number of fake news circulated throughout Facebook has effects on the beginner voters. They found it difficult to distinguish between fake and real news, were easily provoked, were easy to hate, and change their support.